The Development of Altruism with Special Reference to Human Relationships: A 10-Stage Theory - Ma, Hing Keung (Frontiers in Public Health, 2017)
All human relationships involve some form of cost and benefit and altruism forms the foundation upon which human relationships are built. In this paper, a taxonomy of human relationships in terms of altruism was constructed. In the proposed taxonomy, human relationships are categorized into three major groups: primary group, secondary group, and tertiary group. The primary group consists of members that are very closely related to each other either by genetic relatedness (e.g., parents, siblings, and cousins) or social relatedness (e.g., mate and close friends) or both. The secondary group consists of members that are socially related but also less closely related with each other (e.g., people of the same political or religious group, teachers, mentors, acquaintances, neighbors, working colleagues, and strangers). Lastly, the tertiary group consists of members of other species. A 10-stage theory of altruism with special reference to human relationships is proposed. The affective, cognitive, and relationship aspects of each stage are delineated in details. There are two developmental principles of altruism. The first principle states that the development of altruism follows the 10-stage theory and moves from Stage 1: Egoism toward the higher stages of altruism slowly. The second developmental principle states that the taxonomy of human relationships is valid at any stage of altruism development. In other words, people at any stage of altruism are more altruistic toward their kin and mate, and then close friends, extended family members, and so on. They are least altruistic toward enemies and members of non-human species. In summary, the proposed developmental principle of altruism and human relationships is logical and robust. It is formulated based on the major developmental and social psychological theories. The theory has the potential in providing a useful framework for future studies on the development and evolution of human relationships.